AI-Powered Personalized Mobile Education for New Zealand Students - Frank Charles (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2023)
This research aims to develop and evaluate a personalized mobile education system for New Zealand students, utilizing AI and UCD principles. The system will address the limited personalization in existing mobile education solutions, by providing tailored learning content and recommendations based on individual preferences, catering to the diverse needs of students. The study will employ a mixed-methods approach, including user research, persona development, user journey mapping, design, development, and evaluation. Participants, including New Zealand students, parents, and teachers, will be involved in several phases of research to ensure that user-centered design principles are effectively implemented. By demonstrating the potential of AI-powered personalization to improve the learning experience for students, this study contributes to the increasing use of AI algorithms and systems in education.